Delivery of Wnt inhibitor WIF1 via engineered polymeric microspheres promotes nerve regeneration after sciatic nerve crush. (April 2022) - Zhang, Na; Lin, Junquan; Chin, Jiah Shin; Wiraja, Christian; Xu, Chenjie; McGrouther, Duncan Angus; Chew, Sing Yian
Injuries within the peripheral nervous system (PNS) lead to sensory and motor deficits, as well as neuropathic pain, which strongly impair the life quality of patients. Although most current PNS injury treatment approaches focus on using growth factors/small molecules to stimulate the regrowth of the injured nerves, these methods neglect another important factor that strongly hinders axon regeneration—the presence of axonal inhibitory molecules. Therefore, this work sought to explore the potential of pathway inhibition in promoting sciatic nerve regeneration. Additionally, the therapeutic window for using pathway inhibitors was uncovered so as to achieve the desired regeneration outcomes. Specifically, we explored the role of Wnt signaling inhibition on PNS regeneration by delivering Wnt inhibitors, sFRP2 and WIF1, after sciatic nerve transection and sciatic nerve crush injuries. Our results demonstrate that WIF1 promoted nerve regeneration ( p  < 0.05) after sciatic nerve crush injury. More importantly, we revealed the therapeutic window for the treatment of Wnt inhibitors, which is 1 week post sciatic nerve crush when the non-canonical receptor tyrosine kinase (Ryk) is significantly upregulated.